Field testing of different synthetic attractants for mass trapping of common European cockchafer (Melolontha melolontha [L.], Coleoptera, Scarabaeidae) adults. (17th February 2019) - Trdan, Stanislav; Čuk, Jana; Poženel, Anka; Bavcon Kralj, Mojca; Rot, Mojca; Carlevaris, Branko; Žežlina, Ivan; Vidrih, Matej; Laznik, Žiga; Bohinc, Tanja
ABSTRACT: Between 2012 and 2014, we tested the efficacy of different synthetic attractants for the purpose of massive trapping of common European cockchafer adults ( Melolontha melolontha ). The research took place in three different locations in Slovenia (Otlica, Črni Vrh nad Idrijo, Cesta nad Ajdovščino) during flight periods of adult beetles. In the period 2013–2014, we used, on the basis of the preliminary test results (2012), the following chemicals: toluquinone, cis–3–hexen–1-ol, ethyl acetate, toluquinone + cis–3 hexen–1-ol, and ethanol as a control. M. melolontha adults were most abundant in the location Črni Vrh nad Idrijo; the traps in this location caught 18 times more of them than those in the first location and more than six times more than those in the third location. Male insects accounted for 73 to 87% of the trapped specimens. We confirmed the highest efficiency of cis–3–hexen–1-ol in 2013 (43.25 ± 0.08 males/trap), as well as in 2014 (15.00 ± 0.14 males/trap). On the basis of the trapped adult common European cockchafers and the simple economic analysis of applying different synthetic substances for attracting them, we found that independent application of cis-3-hexen-1-ol is the most efficient and cost-effective option for attracting the studied insect pest. Consequently, we recommend it as an attractant in the traps for massive trapping of adult common European cockchafers.